الوسائل التأديبية في الفقه الإسلامي وتطبيقاتها في المملكة العربية السعودية - آل مساعد، فهد بن محمد بن سعود (Ahmad Ibrahim Kulliyyah of Law, International Islamic University Malaysia, 2018)
This research attempts at providing the theoretical and practical approaches that focus on the disciplinary means and methods in the Islamic jurisprudence, and their applications in the Kingdom of Saudi Arabia, in the fields of family affairs, education and work, whereby shedding light on the concept of means and discipline and related terms, In the areas of discipline in family matters, education and employment. It also aims to identify the types of materialistic and non-materialistic means of discipline, the concept of criminal liability and provisions on the use of disciplinary means, and the method of their use with regard to the legal consequences, especially when they are used wrongfully. In accordance with the scientific methodology, the researcher applied the following methods: the inductive method, the analytical method and the comparative method. The study concluded with a set of results. It is also concluded with a set of recommendations, including: the Saudi regulator should formulate such rules and regulations as prescribed by Shari'ah Scholars and regulations regarding personal affairs, which clarify the rights and duties of the people. The Saudi regulator shall also impose disciplinary sanctions that relate to a discipline executors, who often exceed the right and power given to them by Shariah, in which those sanctions will be severe and dissuasive.